A Study of First Referral Units in Border District of Uttar Pradesh, India. - Shukla, Brijesh K; Kaushal, Suneel Kumar; Misra, Sunil Kumar; Chaudhary, Shailendra Singh; Singh, Geetu (Indian Journal of Community Health, 2017)
Background: Health services are designed to meet the health needs of the community through the use of available knowledge and resources. Secondary Level of Health Care essentially including Community health centers (CHCs) constituting the First Referral Units (FRUs) and the Sub-district and district hospital, designed to provide referral health services. First Referral Units provide optimal specialized care to the community to achieve and maintain acceptable quality care. Objective: To assess the available resources and minimum services at FRUs as per IPHS Standards in District Agra. Material & Methods: A Cross- sectional study was conducted in Four FRUs of Agra District, from June 2015 – August 2016. All four FRUs were evaluated for infrastructure, drugs and consumables, equipment, manpower, as per IPHS standards and minimum services provided by first referral units (FRUs). Status of FRUs as against revised (2012) IPHS Standard. Results: All the four FRUs (100%) have their own government building. Availability of drugs and consumable, equipment, were good which was 100% while 25% of FRUs had blood storage facility.50% of FRUs had general surgeon, dental surgeon, gynecologist and anesthetist while 100% of FRUs had medical superintendent, medical officer and availability of staff nurse and pharmacist were 75% and 91.7% respectively among all four FRUs. None of FRUs fulfills the minimum services available as per IPHS norms i.e. emergency obstetric care, blood bank/ blood storage facility, except 24-hourly delivery services which was available at all four FRUs (100%) Conclusion: Physical infra-structure, drugs and consumables, equipment, availability found adequate in all FRUs.Availability of specialist doctor markedly lacking in all FRUs however Paramedical staffs position was better, none of the FRUs meets the minimum criteria for service available at FRUs as set by IPHS standard.